Environment and basic needs in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'The Save study: Relationships between the environment and basic needs satisfaction in the Save Catchment, Zimbabwe'